2018
DOI: 10.1159/000492492
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics of Patients with Acute Esophageal Mucosal Lesion and those with Severe Reflux Esophagitis

Abstract: Background: The term “acute esophageal mucosal lesion (AEML)” includes black esophagitis, and non-black esophagitis characterized by diffuse circumferential erosions without black-appearing mucosa. Black esophagitis is easily diagnosed, whereas non-black esophagitis is often misdiagnosed as severe reflux esophagitis (sRE). The aim of this study was to determine differences in clinical characteristics of patients with AEML and those with sRE. Methods: Thirty-nine patients with sRE and 32 patients with AEML were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Several hypertensive medications (including Ca blockers) exacerbate GERD, causing an increase in gastroesophageal reflux. 1,15,[26][27][28][29] Therefore, the increased prescription rate of PPIs after H. pylori eradication in hypertensive patients might be because of the increased risk of GERD due to the condition of hypertension itself and/or because of the hypertensive medications combined with hypertension. 26,30 The present study did not find a significant influence of Ca blockers on the prescription of PPIs, which suggested that other hypertensive medications than Ca blockers and/or hypertension itself might facilitate PPIs medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several hypertensive medications (including Ca blockers) exacerbate GERD, causing an increase in gastroesophageal reflux. 1,15,[26][27][28][29] Therefore, the increased prescription rate of PPIs after H. pylori eradication in hypertensive patients might be because of the increased risk of GERD due to the condition of hypertension itself and/or because of the hypertensive medications combined with hypertension. 26,30 The present study did not find a significant influence of Ca blockers on the prescription of PPIs, which suggested that other hypertensive medications than Ca blockers and/or hypertension itself might facilitate PPIs medication.…”
Section: Discussionmentioning
confidence: 99%
“…The prescription rate of PPIs after H. pylori eradication was increased in the group of patients with hypertension. Several hypertensive medications (including Ca blockers) exacerbate GERD, causing an increase in gastroesophageal reflux 1,15,26–29 . Therefore, the increased prescription rate of PPIs after H. pylori eradication in hypertensive patients might be because of the increased risk of GERD due to the condition of hypertension itself and/or because of the hypertensive medications combined with hypertension 26,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, differentiating between these diseases is important. Sakata et al reported that an important difference between sRE and AEML is the shape of the esophageal mucosal erosions on the proximal side [7]. sRE is characterized by the formation of spiny erosions (Figure 1), whereas these are absent in AEML (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Antacid medications, including potassium-competitive acid blockers, proton pump inhibitors (PPI), and/or H 2 receptor antagonists, which suppress gastric acid secretion, are widely used to treat gastric acid-related diseases such as peptic ulcers, gastro-esophageal reflux, and Helicobacter pylori-related diseases, including eradication therapy [1][2][3][4][5][6][7]. These medications are useful for prevention of gastroduodenal mucosal damage in patients taking medications such as nonsteroidal anti-inflammatory drugs (NSAID), low-dose aspirin, and antithrombotic agents [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%